Nanocurcumin: A Promising Candidate for Therapeutic Applications - Karthikeyan, Adhimoolam; Senthil, Natesan; Min, Taesun (Frontiers in Pharmacology, 2020)
Curcuma longa is an important medicinal plant and a spice in Asia. Curcumin (diferuloylmethane) is a hydrophobic bioactive ingredient found in a rhizome of the C. longa. It has drawn immense attention in recent years for its variety of biological and pharmacological action. However, its low water solubility, poor bioavailability, and rapid metabolism represent major drawbacks for its successful therapeutic applications. Hence, researchers have attempted to enhance the biological and pharmacological activity of curcumin and overcome its drawbacks by efficient delivery systems, particularly nanoencapsulation. Research efforts so far and data from the available literature have shown a satisfactory potential of nano range formulations of curcumin (Nanocurcumin), it increases all the biological and pharmacological benefits of curcumin, which was not significantly possible earlier. For the synthesis of nanocurcumin, an array of techniques has been developed and each technique has its own advantages and individual characteristics. The two most popular and effective techniques are ionic gelation and antisolvent precipitation. So far, many curcumin nanoformulations have been developed to enhance curcumin delivery, thereby overcoming the low therapeutic eﬀects. However, most of the nanoformulation of curcumin remained at the concept level evidence, thus, several questions and challenges still exist to recommend the nanocurcumin as a promising candidate for therapeutic applications. In this review, we discuss on the different curcumin nanoformulation and its nanocurcumin implications for different therapeutic applications as well as the status of ongoing clinical trials and patents. We also discuss the research gap and future research directions needed to propose curcumin as a promising therapeutic candidate.